Circulation and cross-shelf exchanges in the Malvinas Islands Shelf region. (November 2021) - Palma, Elbio D.; Matano, Ricardo P.; Combes, Vincent
Highlights: Malvinas Is. shelf circulation is dominated by an anticyclonic pattern that intensifies in winter. The largest source for the shelf waters is the northern portion of Drake Passage. There is strong obduction along the southern portion of the shelfbreak. Tracer evolution is driven by the synergetic interaction of tides and winds. There is an important contribution of shelf waters to the Patagonian shelfbreak front. Abstract: The Malvinas Islands Shelf (MIS) encompasses one of the most productive portions of the southwestern Atlantic. Large phytoplankton blooms, which constitute the base of the marine food web, emerge from the northern sector of the MIS and extend hundreds of kilometers northward along the Patagonian shelfbreak. The physical processes contributing to MIS fertilization are poorly understood. Here we use the results of a high‐resolution ocean model to characterize circulation and water mass exchanges between the MIS and the Southern Ocean, as well as to identify the physical processes underlying fertilization of the shelf waters. Model results show that the shelf is characterized by an anticyclonic circulation pattern in the southwestern region that intensifies during summer and weakens during winter. The blocking effect of the islands leads to development of an upwind westward-flowing current in the northern portion of the MIS, recirculation cells in the western portion, and a northward throughflow in the narrow strait separating them. Particle tracking experiments reveal that the northern portion of the Drake Passage is the largest water mass source for the MIS. Passive tracers indicate that the place where the Antarctic Circumpolar Current collides with the MIS is the main site for the outcropping of deep waters. Subsequent outcropping is largely driven by the synergetic interaction of tides and wind forcing. After spreading along the southwestern shelfbreak, the concentration of tracer peaks in the winter and decays during the spring. In summer, the tracer accumulates on the lee of the islands in agreement with satellite images of chlorophyll-a concentration. Additional experiments show that there is an important contribution of MIS waters to the Patagonian shelfbreak front.